A Review of Research on Multi-Modal UAV Technology: From Structural Innovation to Intelligent Control - Xu, Minjun (International Journal of Mechanical and Electrical Engineering, 2026)
By integrating multiple modes of locomotion, such as aerial, ground, and surface or underwater operations, multi-modal unmanned aerial vehicles (UAVs) overcome the inherent limitations of single-mode robots in terms of endurance, terrain adaptability, and operational range. They have thus become a significant research direction in the field of robotics. This paper systematically reviews the recent research progress in multi-modal UAV technology, presenting a comprehensive overview from four dimensions: system configuration, key technologies, challenges, and future trends. In terms of configuration, amphibious aerial-ground, aerial-aquatic, and tri-modal UAVs are classified according to their structural design characteristics, and the advantages, disadvantages, and applicable scenarios of solutions such as wheeled, legged, and morphing structures are analyzed. Regarding key technologies, this review summarizes existing research achievements and their limitations, focusing on core issues including motion planning and trajectory optimization, control system design, and cross-medium communication and perception. Building on this analysis, the paper explores the main challenges currently facing multi-modal UAVs, such as structural lightweighting, robustness during mode switching, energy management, and autonomous decision-making. Finally, it identifies the deep integration of structure and function, intelligent control and autonomous decision-making, collaborative swarm operations, and the application of novel energy sources and advanced materials as critical directions for future development.